Diagnosis, variability, distribution and systematic position of Labiobaetis pulchellus (Müller-Liebenau & Hubbard 1985) (Ephemeroptera, Baetidae, Baetis s. l.) - Kluge, Nikita; Sivaruban, T.; Srinivasan, Pandiarajan; Barathy, S.; Isack, Rajasekaran (Zootaxa, 2023)
A new synonymy to Labiobaetis pulchellus (Müller-Liebenau & Hubbard, 1985) (= L. soldani Kubendran et al. 2014, syn. n.) is established based on examination of imagines reared from larvae in India and Sri Lanka. This species belongs to the tricolor group, which comprises Holarctic species L. tricolor (Tshernova, 1928), L. propinquus (Walsh, 1863), L. calcaratus (Keffermüller, 1972), and some Oriental species.